FAKTOR- FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PEMERINTAH KABUPATEN SUMBA BARAT - Cornelis Tagu Bore; Ni Luh Putu Sri Purnama Pradnyani; Putu Aristya Adi Wasita (Universitas Triatma Mulya, 2022)
This study aims to analyze factors affecting timeliness of financial reporting submission in West Sumba Regency. It is a quantitative research using primary data collected from questionnaires. The sample was determined by purposive sampling technique and obtained 50 respondents. The data analysis uses multiple linear regression with the help of software SPPSS version 26.The research showed that human resources competences, the implementation of government accounting standards, inter-governmental control systems and the utilization if information technology had positive effect on the delivery timeliness of financial reporting submission in West Sumba Regency